(untitled) (Minerva, 2019)
In the present paper the author would like to offer a comparative research of the expression of temporality in the Hippocratic treatises Epidemics. The author has taken as a starting-point the temporal conjunctions as well as several adverbial temporal links (like ἄλλοτε, ἐνίοτε, ἔστιν ὅτε, etc.) in order to find out the relations among the treatises of Epidemics. In summary, the seven treatises of Epidemics, taken as a whole, contain syntactical peculiarities that distinguish them from the rest of the Corpus Hippocraticum. On the other side, from the point of view of the three canonical groups of treatises, which form Epidemics, we have found out that the group formed by Epidemics II, IV & VI bear several syntactical resemblances to Epidemics V & VII, which do not appear in Epidemics I & III. With respect to Epidemics I & III, the contact points between this group and Epidemics V & VII are fewer and less informative. Nevertheless, besides the relations between Epidemics, taken overall, and the internal relations of Epidemics V & VII, it is remarkable the considerably great amount of syntactical hapax that we have documented in Epidemics V & VII, in both parallel and exclusive chapters.